2009
DOI: 10.1021/je800977n
|View full text |Cite
|
Sign up to set email alerts
|

Enthalpies of Formation of DNA and RNA Nucleobases from G3X Theory

Abstract: The Gaussian-3X (G3X) method has been used to calculate accurate values of the gas-phase enthalpies of formation of all five DNA and RNA nucleobases: thymine, adenine, cytosine, guanine, and uracil, whose experimental gas-phase study is a difficult problem because of the low vapor pressures. Only for uracil, the published experimental value agrees well with the theoretical one. However, the revision of available experimental data on enthalpies of formation for compounds in the solid phase and enthalpies of sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 37 publications
1
11
1
Order By: Relevance
“…The earliest Δ f H 298 ° (g) value for uracil was determined to be −59.4 ± 10 kJ/mol . After reconsidering the available literature data, Dorofeeva and Vogt suggested a −69.5 ± 3.5 kJ/mol value. The result of Emel’yanenko is somewhat higher, −66.9 ± 2.1, because of their higher sublimation enthalpy value.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The earliest Δ f H 298 ° (g) value for uracil was determined to be −59.4 ± 10 kJ/mol . After reconsidering the available literature data, Dorofeeva and Vogt suggested a −69.5 ± 3.5 kJ/mol value. The result of Emel’yanenko is somewhat higher, −66.9 ± 2.1, because of their higher sublimation enthalpy value.…”
Section: Resultsmentioning
confidence: 98%
“…Dorofeeva and Vogt, and Emel’yanenko and co-workers list 225.7 and 225.8 kJ/mol, respectively, as the heat of formation of adenine in the gas phase. The first value is based on the combustion calorimetry results of Kirklin and Domalski combined with the sublimation enthalpy of A. Zielenkiewicz et al, while the other is the original result of ref .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous works, the D f H m ðg; 298:15 KÞ values were calculated for DNA and RNA nucleobases [1] and two amino acids [2] by Gaussian-3X (G3X) method. It has been shown that theoretical calculations could be used to test the accuracy of experimental values and recommend more reliable enthalpies of formation for compounds in the solid phase and enthalpies of sublimation.…”
Section: Introductionmentioning
confidence: 99%
“…C2-N1, C4-N3 and C5-N7, C8-N9, may leave the remaining neutral HCN intact.Within the collision energy range studied for adenine and its derivatives, i.e. for the available energy (3.8-68.3 eV), such loss of HCN units is operative since the estimated threshold of the decomposition reaction requires 3.89 eV given that ΔfHg° (C5H5N5) = 225.7 kJ/mol (2.34 eV),41…”
mentioning
confidence: 99%